The Model of Informational Space for Innovation and Design Activities in the University - Shkitsa, L.Ye.; Kornuta, V.A.; Kornuta, O.V.; Bekish, I.O. (Science and Innovation, 2024)
Introduction. The University loses the role of the only source of knowledge in the context of widespread use of network technology for access to information. Simple interfaces for obtaining knowledge on demand provide an opportunity for rapid self-education in the process of realization industrial or domestic tasks. Rethinking the role and place of the university in training engineers and scientists, modernizing of models of information technology achievements’ use by universities in their information systems becomes critically important. Problem Statement. Students are poorly involved in research and innovation activity, the model of organization of the work of universities separates the educational process from other activities. Purpose. To develop a model of scientific and educational information space for innovative and project activity of the community of teaching stuff and university students. Materials and Methods. The methods of logical and comparative analysis have been used. Results. The model of the integrated scientific and educational information space of a technical university with the organization of work on the basis of reliable sources is proposed. Taking into account the possibility of various ways of developing scientific research and the need for the formation of appropriate project teams, the information system for the project activity based on the concept of adaptive case management is proposed. The subsystem of the knowledge base of the training system for drilling equipment designing has been developed. Conclusions. The described models of scientific and educational work provide a project approach to the management of joint work of teaching stuff and students. The introduction of such management model necessitates the use of methods of project-based learning. Further research will aim at developing ways of implementation of project-oriented learning in the educational process of the higher education institution within the existing legislative and regulatory framework.